The Legionella pneumophila IcmSW complex interacts with multiple Dot/Icm effectors to facilitate type IV translocation. - Eric D Cambronne (PLoS Pathogens, 2007)
Many gram-negative pathogens use a type IV secretion system (T4SS) to deliver effector proteins into eukaryotic host cells. The fidelity of protein translocation depends on the efficient recognition of effector proteins by the T4SS. Legionella pneumophila delivers a large number of effector proteins into eukaryotic cells using the Dot/Icm T4SS. How the Dot/Icm system is able to recognize and control the delivery of effectors is poorly understood. Recent studies suggest that the IcmS and IcmW proteins interact to form a stable complex that facilitates translocation of effector proteins by the Dot/Icm system by an unknown mechanism. Here we demonstrate that the IcmSW complex is necessary for the productive translocation of multiple Dot/Icm effector proteins. Effector proteins that were able to bind IcmSW in vitro required icmS and icmW for efficient translocation into eukaryotic cells during L. pneumophila infection. We identified regions in the effector protein SidG involved in icmSW-dependent translocation. Although the full-length SidG protein was translocated by an icmSW-dependent mechanism, deletion of amino terminal regions in the SidG protein resulted in icmSW-independent translocation, indicating that the IcmSW complex is not contributing directly to recognition of effector proteins by the Dot/Icm system. Biochemical and genetic studies showed that the IcmSW complex interacts with a central region of the SidG protein. The IcmSW interaction resulted in a conformational change in the SidG protein as determined by differences in protease sensitivity in vitro. These data suggest that IcmSW binding to effectors could enhance effector protein delivery by mediating a conformational change that facilitates T4SS recognition of a translocation domain located in the carboxyl region of the effector protein.